Analysis of Students’ Learning Loss in Math in Padang City, Indonesia - Sartono, Sartono; Triswandari, Retno; Nisa, Sahrun; Safitri, Serly; Ariani, Yetti; Zainil, Melva; Helsa, Yullys (Mathematics Education Journal, 2024)
COVID-19 caused the learning process to change from a face-to-face learning process to a distance learning process by using various applications. However, this learning process is also considered less effective in math because students’ conceptual understanding is imperfect. The imperfection of this concept caused students to experience learning loss. This research aimed to analyze students’ learning loss in elementary schools in mathematics subjects. This research used a qualitative research design with a case study type of research. This research involved 280 fifth-grade students from 4 elementary schools. The research results showed that students experienced learning loss in understanding geometry and fraction concepts. Students cannot solve math problems if the problem contains two concepts at once. According to the students, they did not understand these three topics well because when studying these topics, they carried out a distance learning process. Based on these findings, researchers concluded that students experienced learning loss in the high category, with 82% students affected. This study highlights the need for teachers to address learning loss that students experience in geometry and fraction materials. Thus, mathematics teachers can prepare learning tools to help students overcome learning loss.